Effect of addition of SiMa filling to styrene - butadiene (SBR) rubber on its mechanical properties and homogeneity - Wafaa Sulaiman; Seham Ali (College of Education for Pure Sciences, 2007)
ABSTRACT In this reaserch the effect of adding the Silica filler with amounts (25,50,75,100)parts per 100 parts of the rubber Styrein-Butadien(SBR),on the mechanical properties and homogenity of the SBR was studied.It was found that the amount 50 parts of Silica per 100 parts of SBR gave the best compound with high homogenity and best mechanical properties with the condition that it should be added to the rubber in its elastic stage and not in its glass stage.